Tích hợp kỹ thuật mạng nơ ron và giải thuật di truyền trong phân tích dữ liệu - Thủy, Nguyễn Thanh; Hà, Trần Ngọc (Journal of Computer Science and Cybernetics, 2016)
In this paper we shall investigate an integration of genetic algorithms into defining neural network structure (number of hidden layers, number of neurons in each layer, neural connection weights). This combination showed its effectiveness in an experimentation for chemical data analysis in comparison with using only back-propagation neural network as shown in [4].